HARGA SAHAM DIPENGARUHI OLEH PENGEMBALIAN ASET DAN RASIO UTANG TERHADAP EKUITAS PERUSAHAAN SUB SEKTOR FARMASI INDUSTRI BARANG DAN KONSUMSI YANG TERDAFTAR DI BEI - Rahma Nisa Larasati; Rosdiana (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
To analyze the effect of Return On Assets and Debt to Equity Ratio on Stock Prices of Companies in the Pharmaceutical Sub-Sector of the Goods and Consumer Industry listed on the Indonesia Stock Exchange. This study used the purposive sampling method. The analytical method used multiple and simple linear regression. The results of this study show that return on asset and debt to equity ratio simultaneously have a significant effect on the stock value of pharmaceutical sub-sector companies in the Goods and Consumer Industry listed on the Indonesia Stock Exchange . While partially return on assets and debt to equity ratio affect stock price.